A heuristic rule-based approach for monitoring of hemodynamic data in cardiothoracic intensive care unit - Abdul Kadir, Rabiah; Al Maweri, Abdul Rahman Ali Ali; Dimon, Mohd Zamrin (Universiti Utara Malaysia, 2012)
Patients in Cardiothoracic Intensive Care Units (CICU) are physiologically weak and require watchful monitoring and support. Such monitoring generates massive amount of data that enable early detection of changes in the patient's condition and provide information that help medical staff to give the treatment and evaluate the response to medical interventions. The countless data gathered from monitoring systems and clinical information systems have created a challenge and are time consuming for clinicians to analyze. This paper discusses the implementation of an intelligent system that has been designed to improve interpretation of clinical data which will then increase the quality and efficiency of the working environment in CICU. The implementation is based on the description state from the cardiologist. This research work extends the cardiologist approach by providing the heuristic rules-based approach to address the treatment. The system is intended to help physicians and CICU staffs to diagnose and track the conditions of patients.